Analisis Kebutuhan Program Promosi Pencegahan Diare pada Anak Berusia di Bawah Dua Tahun - Elfi Rahmawati, Retna Siwi Padmawati, Rendra Widyatama (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Diarrhea is one of environmental based diseases and still the cause of major health problems in Indonesia. It is attributed to the poor condition of basic sanitation, physical environment and the poor behavior of community in personal hygiene. Diarrhea is considered as one of the infectious diseases and the main cause of mortality and morbidity in children under-five particularly under two-years old. Various health promotion activities have been conducted to control diarrhea disease, yet the diarrhea incident rate still high. Even for certain period there has been an increasing number of diarrhea patients.Objective: This research was aimed at describing the community’s need for the health education of diarrhea prevention.Method: This was a qualitative research using case study approach. Data collection was conducted by in depth interview, focus group discussion, observation and document study. Research informants were mothers who have children below two years old and health education stakeholders. Data was analyzed using interactive analysis.Result: The promotion program for diarrhea prevention that has been conducted in Primary Health Care of Piyungan was not able to diminish various inappropriate perceptions and assumptions toward diarrhea. The community could not see the relation between diarrhea with environment and breastfeeding. Community’s need toward diarrhea information was all materials related with diarrhea. The method to convey was through speech that used leaflet, folder and booklet. The information source that suitable to give information was health care provider in regulars meeting every month.Conclusion: the suitable health promotion for diarrhea is speech by health provider using leaflet, booklet and folder. Education material should be focused on diarrhea prevention, especially on the relationship between environment and breastfeeding and diarrhea incidents.Keywords: need assessment, promotion program, diarrhea prevention